Role of felids in the COVID-19 pandemic (FAVE Sección Ciencias Veterinarias, 2022)
In late december 2019, an unusual pneumonia emerged in humans in Wuhan, China, which is caused by a coronavirus (CoV) called SARS-CoV-2. Coronavirus infections are common in animals and humans, being some strains zoonotic. Both domestic (Felis silvestris catus) and wild felids appear to be highly susceptible to SARS-CoV-2 infection, transmitting the infection to other felids. In these species, virus replicates mainly in the upper respiratory tract. Respiratory transmission can be mediated by microdroplets or aerosols, and is mainly linked to close contacts between animals and humans in closed or confined environments. Felids develop titers of neutralizing antibodies and are resistant to reinfection. Despite the potential initial transmission in Wuhan, to date there is no solid evidence of natural transmission from animal to humans, except for minks. It is recommended that animals whose owners are infected with COVID-19 -as well as animals with suspected or confirmed SARS-CoV-2 infection- be kept indoors.
Keywords: felines; SARS-CoV-2; Epidemiology